Insights extraction on cross-cultural interaction through astronomy online labs using data analytics - M. Bakri; Norhaslinda Kamaruddin; M. Hamiz; P. Marlia; A. H. S. Nurhasmiza; Z. Othman; N. A. S. Nilam (Institute of Advanced Engineering and Science, 2019)
Dialogical inquiry on astrology offers the participants to gain not only the intellectual and technological knowledge on the subject matter but also the social benefit of the interaction. Different cultures and values may pose as a challenge for adaptation when the participants start to collaborate in order to complete the group work. Hence, multiple sessions of cross-cultural interaction through Astronomy Online Labs had been conducted to give the participants a standardized platform to discuss and communicate. However, it is imperative to observe the content and frequency of the interaction to ensure both parties (Local and Non-local) benefited from such interaction. The interaction had been recorded and analysed to give us some insights for the improvement of the future participants’ engagement. The visualization techniques such as word cloud, word forest, timeline as well as Venn diagram approaches had been used and it is observed that the participants are actively communicating with the Non-local slightly dominating the session. It is hoped that the analysis tool can be embedded in the platform that it can provide dynamic analysis on the go while interaction happens so the moderator can steer the interaction to the intended topic.